2022
DOI: 10.3389/fenvs.2022.1028750
|View full text |Cite
|
Sign up to set email alerts
|

The impact of digital economy development on carbon emissions -- based on the Yangtze River Delta urban agglomeration

Abstract: The dual carbon target has been the focus of domestic attention since it was proposed. At the same time, the digital economy based on new technologies such as the Internet and big data has become an important engine to boost China’s high-quality economic development. While the digital economy is promoting the development of the urban economy, can it also promote the low carbon development of cities in China? Based on panel data and multiple econometric models of 26 cities in the Yangtze River Delta urban agglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Existing research has mainly utilized the entropy method and principal component analysis to measure the level of the DE's development [35][36][37][38]. Subjective weighting methods, such as principal component analysis, may create problems such as randomness due to human factors [35,39].…”
Section: The Entropy Methodsmentioning
confidence: 99%
“…Existing research has mainly utilized the entropy method and principal component analysis to measure the level of the DE's development [35][36][37][38]. Subjective weighting methods, such as principal component analysis, may create problems such as randomness due to human factors [35,39].…”
Section: The Entropy Methodsmentioning
confidence: 99%
“…The carbon emission sources of cities were set as direct and indirect energy consumption. Direct energy includes liquefied petroleum gas, coal, and natural gas, and indirect energy includes electricity and heat (Zha et al, 2022). Carbon emissions from direct energy sources were mainly calculated based on the carbon emission conversion coefficients of various energy sources published in the 2006 IPCC Guidelines for National Greenhouse Gas Inventories.…”
Section: Dependent Variablementioning
confidence: 99%
“…On the other hand, some studies have noted the spillover effects of the development of the digital economy. Such as Zha et al ( 2022 ) found that the development of digital economy can not only abate the carbon emission intensity of the specific region, but also effectively improve the environmental performance of surrounding cities. Shen et al ( 2022 ) found that the development of local digital economy is highly correlated with economic development level, and the development of digital economy has a positive spillover effect on environmental performance in surrounding areas.…”
Section: Literature Reviewmentioning
confidence: 99%